Assessment of frailty in community-dwelling older adults by age group and different instruments - Martins, Andréia Christiane Amâncio; Santos, Brenda Gomes dos; Prado, Maria Eduarda Fernandes do; Carvalho, Luciane Balieiro de; Santos, Marcelo Rocha; Cardoso, Leonardo Lamêgo; Santiago, Marianne Caldeira de Faria; Boitrago, Sarah Caroline Oliveira de Souza; Costa, Fernanda Marques da; Carneiro, Jair Almeida (Seven Editora, 2024)
Objective: To analyze frailty in community-dwelling older adults by age group, comparing the degree of agreement and correlation between the EFS and IVCF-20 instruments. Methods: This is a cross-sectional study nested in a population-based cohort, with probabilistic, cluster, and two-stage sampling. The first stage considered the census tract as the sampling unit; while the second determined the number of households according to the population density of elderly individuals. The Kappa statistic analyzed the degree of agreement and Pearson's coefficient evaluated the correlation between the instruments. Results: A total of 394 community-dwelling elderly were allocated, with a predominance of females (66.7%) and 65 to 69 years of age (26.4%). The prevalence of frailty was higher among the age group of 90 years and over, being 44.4% in both the IVCF-20 and the EFS. There was a higher prevalence of frailty in the elderly aged between 60 and 79 years and slightly higher between 85 and 89 years when using EFS. The Kappa statistic showed a low agreement index (0.399) between the instruments in the age group between 65 and 69 years, while in the age group aged 90 years or older, there was a strong agreement (Kappa 0.775). The IVCF-20 and EFS instruments showed strong agreement and showed greater coherence in the assessment of frailty in the long-lived elderly. Conclusion: The IVCF-20 instruments and the EFS showed moderate to strong agreement and positive correlation. In the age groups between 80 and 85 years and 90 years and over, the prevalence of frailty was the same for both instruments, which demonstrates the strong association between frailty and advanced age. DOI:https://doi.org/10.56238/sevened2024.007-080